Umbilical cord wrapping around the neck and trunk as the cause of multi-site perinatal trauma – a case report - Wójtowicz-Marzec, Monika; Berendt, Agnieszka; Zarzycka, Danuta; Ścibak, Izabela A. (Prenatal Cardiology, 2023)
Nuchal cord is a relatively frequent phenomenon detected in the prenatal period and in newborns in the perinatal period. Most patients do not demonstrate any post-traumatic lesions related to umbilical cord wrapping. The patient referred to in this study suffered multiple haemorrhagic injuries after the delivery, which contributed to his extended stay at the Hospital Department. An additional objective of the article is to demonstrate ultrasound diagnostic options from the very first moment after childbirth. A sequence of ultrasound examinations allowed the monitoring of receding postnatal lesions in the patient without exposing him to X-rays.